The e-code : - Vitale, Joe (J. Wiley, 2005)
The E-Code brings together the combined wisdom of 33 Internet marketing superstars to reveal how they make money online-using nothing but the power of e-mail. Each succinct chapter presents one moneymaking strategy or concept and offers step-by-step guidance on implementing it for maximum profits. If you have a product or service to sell, the Internet gurus in this book will show you how to sell it-no matter what it is. And even if you don't have your own original product idea, don't worry. Inside you'll find a wealth of quick and effective ideas for creating something that other people will definitely pay for. Using tactics like viral product marketing and online auctions, anyone can make extra money online-and you can too. This is not a get-rich-quick scheme; it's a make-money-quick scheme. It could be a little, or it could be a lot, but you will definitely profit when you learn how to: Develop and sell a product online; Target your customers; Promote your product; Market to niche audiences; Create an e-marketing business plan.